1986
DOI: 10.1002/eji.1830160903
|View full text |Cite
|
Sign up to set email alerts
|

IgE receptors on human lymphocytes III. Expression of IgE receptors on mitogen‐stimulated human mononuclear cells

Abstract: Human peripheral blood mononuclear cells (PBMC) were tested for the expression of Fc epsilon-receptor (Fc epsilon R) after stimulation with various mitogens in the absence of IgE. Fc epsilon R were found on virtually all the cells from 19 Epstein-Barr virus-transformed B cell lines including those derived from cord blood, from one agamma-globulinemic patient and VDS-0 pre-B cells. Hence, the data clearly indicate that Fc epsilon R may be expressed on very immature B cells. PBMC cultures stimulated with either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 14 publications
(6 reference statements)
3
10
0
Order By: Relevance
“…Results similar to ours have been obtained with B lymphocytes [21,35]. Moreover, Delespesse et al [36] found evidence that IgE protects FceRII from prote olysis; they have also recently described a FceRI ¡-as sociated proteolytic activity [37].…”
Section: Discussionsupporting
confidence: 76%
“…Results similar to ours have been obtained with B lymphocytes [21,35]. Moreover, Delespesse et al [36] found evidence that IgE protects FceRII from prote olysis; they have also recently described a FceRI ¡-as sociated proteolytic activity [37].…”
Section: Discussionsupporting
confidence: 76%
“…Inasmuch as an increase in the percentage o f .~c e~( + j cells b a s observed only in allergic younger children (0-2 yr) in whom intensive sensitization might be occurring, it may be a reaction related to this sensitization. Activation of T cells by allergens during the sensitizing process may cause the increase in FctR(+) cells because FctR was induced on lymphocytes by soluble factors secreted by activated T cells (10)(11)(12). Additional investigation is required in order to confirm this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…Upon incubation at 37°C, freshly isolated and highly purified B lymphocytes rapidly loose their FctR II [11]; this is associated with the disappearance of Fc(;R II mRNA and the release of IgE-BFs in the culture supernatant [12]. Further studies showed that the disappearance of surface FcfR II was not due to their internalization, but rather to their shedding.…”
Section: Regulation Of Fc R II Expressionmentioning
confidence: 99%
“…Further studies showed that the disappearance of surface FcfR II was not due to their internalization, but rather to their shedding. The latter was significantly reduced by incubating the cells with IgE [11], whereas it was increased by pretreat ment of the cells with inhibitors of N-linked glycosylation like tunicamycin, swaisonine, and castanospermine [Letellier and Delespesse, unpubl. observations].…”
Section: Regulation Of Fc R II Expressionmentioning
confidence: 99%
See 1 more Smart Citation